Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Konsumtif Siswa-Siswi Di SMK Negeri 1 Kota Tidore Kepulauan - Nasarudin, Urna; Hasan, Muhammad Hi.; Ruray, Titiek Arafiani (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the influence of Financial Literacy and Lifestyle on the Consumptive Behavior of Students at SMK Negeri 1 Kota Tidore Kepulauan. This study uses a quantitative approach. The sampling method uses the Slovin formula. The results of the study indicate that the Financial Literacy variable has a significant influence on the consumptive behavior of students at SMK Negeri 1 Kota Tidore Kepulauan. This is evidenced by the T-value greater than T-table, namely 2.960>1.971 and a significance value of 0.003 <0.05, Lifestyle has a significant influence on the consumptive behavior of students at SMK Negeri 1 Kota Tidore Kepulauan. This is evidenced by the T-value greater than T-table, namely 4.323>1.971 with a significance value of 0.000 <0.05, Financial literacy and lifestyle variables have a significant influence on the consumptive behavior of students at SMK Negeri 1 Kota Tidore Kepulauan. This is proven by the calculated F value being greater than Ftable, namely 21.050 > 2.65, so H0 is rejected and Ha is accepted, so it can be interpreted that financial literacy and lifestyle have a simultaneous influence on the consumer behavior of students at SMK Negeri 1.